JAK2 Mediates the Regulation of Pept1 Expression by Leptin in the Grass Carp (Ctenopharyngodon idella) Intestine - Wen-jie Luo; Wen-jie Luo; Peng Song; Zhi-min He; Shen-ping Cao; Jian-zhou Tang; Wen-qian Xu; Ding Xiong; Fu-fa Qu; Da-fang Zhao; Zhen Liu; Jian-zhong Li; et al. (Frontiers in Physiology, 2020)
Oligopeptide transporter 1 (Pept1) is located on the brush border membrane of the intestinal epithelium and plays an important role in dipeptide and tripeptide absorption from protein digestion. In this study, we cloned and characterized the cDNA sequence of Janus kinase 2 (JAK2) from Ctenopharyngodon idella. The expression patterns of JAK2 in various tissues and developmental stages were characterized by quantitative real-time PCR (qRT-PCR). The mRNA expression levels of JAK2 and Pept1 regulated by leptin in the intestine were also analyzed in vitro and in vivo. The cDNA sequence of JAK2 is 3378 bp in length, and the mRNA of JAK2 was broadly expressed in all tissues and embryonic stages of C. idella analyzed. In addition, we found that leptin regulated expression of JAK2 and Pept1 in the intestine; Pept1 expression was down-regulated by the JAK2 inhibitor AG490 in vivo and in vitro. Furthermore, luciferase experiments showed that overexpression of the JAK2 gene significantly upregulated the activity of the Pept1 5′ regulatory sequence in C. idella. In conclusion, these results may help in elucidating the regulatory effect of the leptin-mediated JAK2 pathway on intestinal Pept1 expression in C. idella and the molecular mechanism of peptide transport by the intestinal transporter Pept1 in fishes.